Quality of life in women with nausea and vomiting from pregnancy - Mojgan Naeimi rad; Minoor Lamyian (Babol University of Medical Sciences, 2015)
Introduction: Nausea and vomiting in early pregnancy is a common complaint, affecting approximately 50-80% of pregnant women. The aim of this study was to determine the effect of the severity of nausea and vomiting from pregnancy on the quality of life during the first trimester of pregnancy. Methods: An analytical study was conducted on pregnant women with nausea and vomiting from pregnancy (NVP) during their first 12 weeks. These pregnant women were receiving prenatal care at the prenatalogy ward of Rouhani Hospital, which is affiliated to Babol University of Medical Sciences. The women were asked to complete a visual analogue scale questionnaire to report their intensity of nausea within the last 24 hours. The severity of NVP was measured by a structured questionnaire. A Health-Related Quality of Life for Nausea and Vomiting during Pregnancy (NVPQOL) questionnaire was also used to measure the quality of Life of pregnant women with NVP. Low scores in all domains of NVPQOL and the overall quality of life evaluation mean better quality of life. A total number of 80 women with NVP, who were within the age range between 18 to 35, were randomly selected for the purpose of this study. Results: The mean total score of NVPQOL was 95.5±15.69. The total quality of life score in women with severe nausea (p = 0.003) and sever vomiting (p = 0.029) was higher than that of the mild/moderate group. A statistically significant result was found in the mean scores of the fatigue domains between the women with mild/moderate and severe nausea groups (P = 0.001). The women with severe vomiting also had significantly higher mean scores of the physical symptoms (P = 0.027) and limitation (P = 0.027) domains compared with those with low/moderate vomiting. Conclusion: The finding showed that the NVPQOL score was correlated with the severity of NVP symptoms. It is, therefore, very important that we, in our clinical practices, consider the impact of NVP on Iranian woman's quality of life in order to provide them with optimal management in case the need arises.